FAKTOR PENYEBAB PELECEHAN SEKSUAL TERHADAP ANAK - Fauziah, Syarifah (An - Nisa`, 2016)
This paper examines the causes of sexual abuse in children. Sex is a natural part of human life. Because God created man as a creature of sex (gender) and sexual creates in maintaining the continued existence of mankind. However, sometimes there are some people experience sek wrong orientation to the outlet needs inclined to abuse and even sexual abuse in children. This paper will address the causal factors of sexual abuse against children